Assessing equity in health, wealth, and civic engagement: a nationally representative survey, United States, 2020. - Stopka, Thomas J.; Feng, Wenhui.; Corlin, Laura.; King, Erin.; Mistry, Jayanthi.; Mansfield, Wendy.; Wang, Ying.; Levine, Peter.; Allen, Jennifer D. (Tufts University. Tisch Library., 2022)
Keywords: Equity, Health, Wealth, Civic engagement, Nationally representative survey.; Springer Open.